Bioethical foundations application for practice of critical care in ICU patients - García Martínez, María Araceli; Rebolledo Malpica, Dinora Margarita; Pérez Ruiz, Marcos Elpidio; Arteaga Yanez, Yanetzi Loimig; Condo León, Carmen de Lourdes; Muñiz Granoble, Gloria Janeth (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: Most critically ill patients are not located in time, space and person, and even some are unconscious, which makes them vulnerable to moral and ethical performance of their caregivers. Objective: To describe the nursing bioethical behavior in the patient care in intensive care unit of Guayaquil Specialty Hospital "Dr. Abel Gilbert Pontón", Ecuador. Methods: This was a qualitative research, of a clinical ethnography type, for which four nurses working in intensive care unit of said hospital were selected. The information was collected with open interviews and interpreted through a categorization process. Results: The results show the following categories: First, that the commitment in nurse-patient relationship when providing care in the critical units reflects a moral quality of bioethical and humanizing care. Second, that empathy attitudes and patient acceptance as a recipient of care recognize bioethical and humanizing values. Third, there is emotional, social and cultural understanding of what it means to be in a critical care situation according to patient perspective and his family. Conclusions: It is confirmed that nursing care bioethics is a rational and critical reflection of human values implicit in the needs satisfaction perception of critical patient, which entails to provide care with warmth, with a disposition to understand it and to do it feel comfortable, allowing to establish human links between patient-nurse.